A Review of the Current Status of Peste des Petits Ruminants Epidemiology in Small Ruminants in Tanzania - Idoga, Enokela S.; Armson, Bryony; Alafiatayo, Ruth; Ogwuche, Adah; Mijten, Erik; Ekiri, Abel B.; Varga, Gabriel; Cook, Alasdair J. C. (Frontiers in Veterinary Science, 2020)
Peste des petits ruminants (PPR) is a highly contagious viral disease of sheep and goats with high mortality. The disease is of considerable economic importance in areas such as Tanzania, where small ruminant products are important for sustainable livelihoods. This review assesses current knowledge regarding the epidemiology of PPRV in Tanzania, highlighting the challenges with respect to control and suggesting possible interventions. Thirty-three articles were identified after literature searches using Google Scholar and PubMed. Studies revealed that PPRV is endemic in sheep and goats in Tanzania, although seropositivity has also been reported in cattle, camels, buffalo, Grant’s gazelle, wildebeest and impala, but with no clinical manifestation. Three lineages (lineage II to IV) of PPRV have been identified in Tanzania, implying at least two separate introductions of the virus. Diagnosis of PPR in Tanzania is mostly by observation of clinical signs and lesions at post mortem. Risk factors in Tanzania include age, sex, species and close contact of animals from different farms/localities. Although there is an efficacious vaccine available for PPR, poor disease surveillance, low vaccine coverage, and uncontrolled animal movements have been the bane of control efforts for PPR in Tanzania. There is need for collaborative efforts to develop interventions to control and eradicate the disease. The establishment of a national reference laboratory for PPR, conduct of surveillance, the development of high-quality DIVA vaccines, as well as execution of a carefully planned national vaccination campaign may be key to the control and subsequent eradication of PPR in Tanzania and achieving the global goal of eradicating PPR by 2030.